2015
DOI: 10.1016/j.csi.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Designing for designers: Towards the development of accessible ICT products and services using the VERITAS framework

Abstract: Among the key design practices which contribute to the development of inclusive ICT products and services is user testing with people with disabilities. Traditionally, this involves partial or minimal user testing through the use of standard heuristics, employing external assisting devices, and the direct feedback of impaired users. However, efficiency could be improved if designers could readily analyse the needs of their target audience as part of a highly iterative design process. The VERITAS framework simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
7
0
3
Order By: Relevance
“…One of the main limitations of our study was its connection to one university only, which might affect the generalizability of our results, although most of the results confirmed previous work conducted on this topic [30,31,[38][39][40]. Another limitation is that we only had 19 respondents, which might pose some threats to validity; however, we tried to mitigate this by using interviews, which helped us confirm some of the results and revealed some new insights.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…One of the main limitations of our study was its connection to one university only, which might affect the generalizability of our results, although most of the results confirmed previous work conducted on this topic [30,31,[38][39][40]. Another limitation is that we only had 19 respondents, which might pose some threats to validity; however, we tried to mitigate this by using interviews, which helped us confirm some of the results and revealed some new insights.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, the authors of [38] reported that only 16% of the participants were familiar with WCAG, and 13% and 7% were familiar with ATAG and UAAG, respectively. A lack of knowledge about WCAG among web developers has continued to be the trend, even in more recent surveys [39,40].…”
Section: Teacher 1: "I Am Not Familiar With Any Disability Policies Omentioning
confidence: 99%
“…One of the most recognized UEMs concern the family of user testing methods [26]- [28], in particular think-aloud protocol [29]- [31], question-asking protocol [32]- [34], performance measurement [35]- [37], log analysis [38]- [40], eye tracking [41]- [43], and remote testing [44]- [46]. Secondly, inspection methods, intended to be used by experts [47], refers to heuristic evaluation [48]- [50], cognitive walkthrough [51]- [53], perspective-based inspection [54]- [56], and guideline reviews [57]- [59]. Thirdly, inquiry methods, designed to gathering subjective data from users, utilize both quantitative (questionnaires [60]- [62]) and qualitative (interviews [63]- [65] and focus groups [66]- [68]) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…La accesibilidad universal se refiere a la condición de los entornos, procesos, productos, servicios, objetos, instrumentos, herramientas, dispositivos, etc. para ser comprendidos y utilizados por todos de manera cómoda, natural, autónoma y segura, lo cual requiere que el diseño desde el principio tenga en cuenta la funcionalidad de las personas, cabe notar que los criterios de diseño dependen también del entorno y del avance tecnológico (AENOR, 2007), sin embargo este proceso es difícil en la práctica en cuanto a la determinación de requisitos y la realimentación con este segmento poblacional (Scott, Spyridonis & Ghinea, 2015), dependiendo de la naturaleza de la discapacidad las técnicas de diseño se hacen difíciles de usar, en el caso de diseño de TIC, no existe técnica algunas de diseño para individuos con discapacidad (Dekelver et al, 2015), los diseñadores deben superar éstas limitaciones, pues el turismo accesible es un derecho social y significa facilitar el acceso para las personas, sin importar género, edad, condiciones físicas, etc. con el objetivo del disfrute de experiencias turísti-cas (Menzel & Weldig, 2011).…”
Section: El Turismo Accesibleunclassified